Multiculturalism: A comparative analysis of western countries and Kazakhstan - Elzhasovna Kukusheva, Nazira; Sheryazdanova, Gulmira Rustemovna; Byulegenova, Bibigul Bisenbayevna; Kakimzhanovа, Margarita Kabdulayevna; Turgaleyeva, Akmaral Turgaibekovna (Opción, 2019)
The article seeks to confirm the hypothesis that multiculturalism can be viewed as the idea of nation-building in multinational post-communist countries that gained independence after the fall of the Soviet Union via comparative qualitative research methods. Based on the analysis of current domestic and foreign policy in Kazakhstan, multiculturalism is shown to be an idea of nation-building in a multinational post-communist country of the former USSR. In conclusion, the negative experience of some countries is indicative not of a failure of the multiculturalism idea, but the failed attempt to apply its liberal ideas by conservative politicians.